Metal-based composite material as well as preparation method and application thereof
By introducing nanodiamond particles into the metal-based anode material, using its amorphous carbon layer to improve the electrolyte wetting ability and diamond core to improve structural stability, the problems of poor electrolyte wetting ability and structural instability of metal-based anode materials in the prior art are solved, and higher electrochemical performance and safety are achieved.
Patent Information
- Application Number
- CN202411946504.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-12-27
AI Technical Summary
The existing metal-based anode materials have poor electrolyte wetting, slow cation diffusion kinetics and structural instability caused by volume expansion in secondary batteries, which limit their battery performance.
The composite structure of nanodiamond particles and metal matrix is adopted to improve the wetting of the interface electrolyte through the amorphous carbon layer of nanodiamond particles, and the structural damage caused by volume expansion is suppressed through the hardness and chemical stability of the diamond core.
It significantly improves the electrochemical stability, structural stability and high-rate charging and discharge performance of the material, reduces the risk of thermal runaway, and ensures the safety and stability of the material under high load or high temperature conditions.
Smart Images

Figure CN119742349A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of composite materials, and in particular to a metal-based composite material and a preparation method and application thereof. Background Art
[0002] In the field of new energy batteries, secondary batteries have attracted much attention due to their efficient energy storage mechanism and cost advantages. This type of battery uses the rocking movement of metal cations between the negative electrode and the positive electrode or the reversible redox reaction of anions and metal cations at the positive and negative electrodes to achieve energy storage and release. Metals with alloying effects, such as tin, antimony, bismuth, aluminum, zinc, etc., have attracted much attention because of their high alloying theoretical capacity. For example, tin (Sn) as a negative electrode material for secondary batteries is considered a promising choice due to its high theoretical specific capacity (about 994 mAh / g for lithium storage and 847 mAh / g for sodium storage). However, tin has problems such as poor electrolyte wettability, significant volume expansion (up to 300%), and slow diffusion kinetics of metal cation storage in applications, which limit its performance in batteries. Poor contact between tin and electrolyte and slow metal cation storage reaction kinetics will affect the battery rate performance. Its significant volume expansion during charging and discharging can cause the electrode structure to rupture, thereby affecting the cycle stability and service life of the battery.
[0003] At present, researchers have modified alloy metal negative electrode materials through various methods to improve their electrochemical properties, including nano-sizing, alloying, and coating technologies. For example, existing technologies involve increasing the specific surface area of materials by nano-sizing metal particles such as tin, antimony, and bismuth, improving the contact between electrodes and electrolytes, and thus improving battery performance; another type of technology improves the cycle stability and electrochemical reaction activity of alloys by alloying (such as tin-antimony alloys or tin-zinc alloys) to alleviate volume expansion and enhance ion diffusion capacity; in addition, there are also technologies that propose to use carbon-based coatings or other nanomaterials to coat alloy metals to enhance their electrode stability, reduce electrolyte corrosion, and increase ion conduction speed. Although these modification methods have improved the performance of alloy metal negative electrodes to a certain extent, they still have many problems. For example, although nano-sizing technology increases the specific surface area of alloys and the wettability of electrolytes, it usually requires complex preparation processes and special equipment, and faces high costs in large-scale production. In addition, although the alloying strategy effectively alleviates the problem of volume expansion, due to the diversity of alloy components, it is often necessary to finely control the ratio and preparation process, which also makes the preparation process complicated and costly. Although the coating method can improve the surface properties of the electrode, it usually faces challenges such as poor uniformity of the coating layer and difficulty in controlling the thickness, which in turn affects the overall performance of the electrode.
[0004] In summary, although the existing modification methods have achieved certain results in improving the performance of metal-based negative electrode materials such as tin, they still involve complex preparation processes and high costs, and have not fully solved the problems of slow cation diffusion kinetics of alloy-type metal materials and structural instability under high-rate charge and discharge conditions. Therefore, the development of a new metal-based composite negative electrode material with optimized structure and performance is of great significance for promoting the commercial application of secondary battery technology. Summary of the invention
[0005] The present invention aims to solve the problem that alloy metals in the prior art have poor wettability with electrolytes, poor cation diffusion kinetics, and large volume expansion when used as negative electrode materials for secondary batteries, resulting in poor battery cycle and rate performance. To this end, one of the purposes of the present invention is to provide a metal-based composite material that has good wettability with electrolytes, good structural stability, and good electrochemical performance.
[0006] A second object of the present invention is to provide a method for preparing the above-mentioned metal-based composite material.
[0007] A third object of the present invention is to provide a negative electrode material.
[0008] A fourth object of the present invention is to provide a battery.
[0009] In order to achieve the above object, the technical solution adopted by the present invention is:
[0010] The first aspect of the present invention provides a metal-based composite material, comprising a base material and an active material loaded on the base material; the active material comprises a metal matrix and nano-diamond particles distributed in the metal matrix; the nano-diamond particles comprise a diamond core and an amorphous carbon layer, and the amorphous carbon layer covers at least a portion of the surface of the diamond core.
[0011] The metal matrix composite material according to the first aspect of the present invention has at least the following beneficial effects:
[0012] The present invention utilizes the amorphous carbon layer on the surface of nano-diamond particles, which can effectively improve the wettability of the interface electrolyte, promote the formation of a uniform and stable solid electrolyte interface (SEI) film, and improve the electrochemical stability of the material; and the diamond core has the characteristics of high hardness and good chemical stability, which inhibits the cracks and structural damage caused by the volume expansion of the material, and effectively improves the structural stability of the composite material. In addition, the present invention significantly increases the electrochemical contact area of the material through the composite structure of nano-diamond particles and metal matrix, and optimizes the transmission path of metal cations. Specifically, the introduction of nano-diamond particles is conducive to the formation of a rich heterogeneous interface, providing a fast metal cation diffusion path, thereby improving the high rate charge and discharge performance of the battery; and the introduction of diamond particles can also induce the heterogeneous nucleation of the metal matrix, inhibit excessive grain growth, effectively deal with the volume expansion and stress gradient caused by the alloying reaction, and improve the overall stability of the structure; and the high thermal conductivity of nano-diamond particles also helps to enhance the heat dissipation capacity and thermal stability of the composite material, reduce the risk of thermal runaway, and ensure the safety and stability of the material under high load or high temperature conditions.
[0013] In some embodiments of the present invention, the average particle size of the nano-diamond particles is 0.5 to 200 nm.
[0014] In some embodiments of the present invention, the ratio of the thickness of the amorphous carbon layer to the diameter of the diamond core is 1-40%.
[0015] In some embodiments of the present invention, the nano-diamond particles are distributed in the metal matrix in a content gradient that gradually decreases from the surface to the interior.
[0016] The design of the nano-diamond particle content gradient of the present invention is not only conducive to improving the wettability of the material with the electrolyte, but also can optimize the mechanical strength and electrochemical properties of the material, effectively reduce stress concentration in the material, enhance the anti-fracture performance of the overall structure, and ensure that the material has good stability and high-rate performance during the battery cycle.
[0017] In some embodiments of the present invention, the content of nano-diamond particles on the surface of the metal substrate is 10-80%.
[0018] In some embodiments of the present invention, the total content of nano-diamond particles in the metal matrix is 1-50%.
[0019] In some embodiments of the present invention, the thermal conductivity of the nano-diamond particles is 300-3000 W / m·K.
[0020] In some embodiments of the present invention, the nano-diamond particles are prepared by a method comprising the following steps: reacting a nano-diamond raw material with an acid to obtain the nano-diamond particles.
[0021] Due to the oxidation effect of acid, the surface carbon atoms of the diamond raw material will be rearranged, thereby generating an amorphous carbon layer structure rich in polar functional groups. This amorphous carbon layer structure rich in polar functional groups can effectively improve the interface wettability between the material and the electrolyte, thereby facilitating the formation of a uniform and stable SEI film.
[0022] In some embodiments of the present invention, in the method for preparing the nano-diamond particles, the acid includes sulfuric acid, nitric acid or a combination thereof.
[0023] In some embodiments of the present invention, in the method for preparing the nano-diamond particles, the reaction time of the nano-diamond raw material and the acid is 1 to 20 hours.
[0024] By adjusting the reaction time of the nanodiamond raw material and the acid, the thickness of the amorphous carbon layer can be adjusted.
[0025] In some embodiments of the present invention, the metal matrix includes at least one metal element selected from the group consisting of tin, antimony, bismuth, aluminum, and zinc.
[0026] The present invention can use different metal materials as the metal matrix, especially tin, antimony, bismuth, aluminum or zinc or their alloys. These metal matrices of different materials can support the performance requirements of different batteries such as sodium-based, lithium-based, calcium-based, potassium-based, zinc-based, etc., and obtain good specific capacity and cycle stability.
[0027] In some embodiments of the present invention, the grain size of the metal matrix presents a gradient structure that gradually decreases from the inside to the surface.
[0028] Due to the introduction of nano-diamond particle phase into the metal matrix, the heterogeneous nucleation of the metal matrix phase is induced, thereby increasing the nucleation density and inhibiting grain growth. In the area with high nano-diamond particle content, the metal matrix phase has a smaller crystal grain size, thereby forming a gradient structure in which the metal matrix grain size gradually refines from the inside to the surface, forming a performance distribution that is strong on the outside and tough on the inside, which can well adapt to the volume expansion and stress gradient caused by the alloying reaction and improve the structural stability.
[0029] In some embodiments of the present invention, the metal matrix contains heterogeneous nucleation sites; in some specific embodiments of the present invention, the density of the heterogeneous nucleation sites in the metal matrix is 10 8 ~10 12 Pieces / cm 2 .
[0030] In some embodiments of the present invention, the substrate material comprises a porous material or a non-porous material; in some specific embodiments of the present invention, the substrate material is selected from porous materials.
[0031] In some embodiments of the present invention, the porous material includes at least one of porous aluminum, porous copper, porous nickel or porous stainless steel; in some specific embodiments of the present invention, the porous material is selected from porous aluminum.
[0032] In some embodiments of the present invention, the non-porous material includes at least one of aluminum foil, copper foil, titanium foil, stainless steel foil, platinum foil, zinc foil, gold foil, nickel mesh, tungsten mesh, graphene film, carbon cloth or carbon paper.
[0033] The second aspect of the present invention provides a method for preparing the metal-based composite material described in the first aspect of the present invention, comprising the following steps: using a solution containing a metal salt and nano-diamond particles as a plating solution and a base material as an electrode to perform electroplating treatment to obtain the metal-based composite material; the metal elements in the metal salt include the metal elements in the metal matrix.
[0034] The method for preparing the metal matrix composite material according to the second aspect of the present invention has at least the following beneficial effects:
[0035] The preparation method provided by the present invention has a simple process and low cost, and can produce a metal-based composite material with excellent electrochemical performance and wettability, and has good application prospects in the preparation of high-performance electrode materials and batteries.
[0036] In some embodiments of the present invention, the current density of the electroplating treatment is 1 to 30 mA / cm 2 .
[0037] In some embodiments of the present invention, the deposition time of the electroplating process is 5 to 40 minutes.
[0038] In some embodiments of the present invention, the plating solution further contains gelatin; in some specific embodiments of the present invention, the mass content of gelatin in the plating solution is 0.1-5%.
[0039] The third aspect of the present invention provides a negative electrode material, comprising the metal-based composite material described in the first aspect of the present invention, or the metal-based composite material prepared by the preparation method described in the second aspect of the present invention.
[0040] The negative electrode material according to the third aspect of the present invention has at least the following beneficial effects:
[0041] The metal-based composite material provided in the present invention has good comprehensive properties such as structural stability, cycle performance, high-rate charge and discharge performance and safety performance, and can be used to prepare negative electrode materials with excellent electrochemical performance.
[0042] In some embodiments of the present invention, the negative electrode material does not include a conductive agent and a binder.
[0043] The negative electrode material provided in the present invention has good structural stability and electrical conductivity, and can obtain good electrochemical performance and energy density without adding additional conductive agents and binders.
[0044] The fourth aspect of the present invention provides a battery comprising a positive electrode material, an electrolyte and the negative electrode material according to the third aspect of the present invention.
[0045] The battery according to the fourth aspect of the present invention has at least the following beneficial effects:
[0046] The battery prepared by using the negative electrode material of the present invention has good structural stability and electrochemical performance, especially has excellent specific capacity and cycle performance.
[0047] In some embodiments of the present invention, the positive electrode material includes at least one of graphite, sodium cobalt oxide, sodium nickel manganese oxide, sodium nickel sulfide, sodium manganese oxide, sodium iron phosphate, sodium nickel iron cyanide, vanadium-based oxide or sodium ferric fluoride.
[0048] In some embodiments of the present invention, the battery includes at least one of a sodium ion battery, a lithium ion battery, a calcium ion battery, a potassium ion battery, or a zinc ion battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] Figure 1 The schematic diagram of the structure of the tin-based composite negative electrode material of Example 1 of the present invention is as follows Figure 1 shown.
[0050] Figure 2 This is a TEM image of the nano-diamond particles of Example 1 of the present invention.
[0051] Figure 3 This is a diagram showing the wettability of the composite negative electrode material and the electrolyte in Example 1 of the present invention and Comparative Example 1.
[0052] Figure 4 This is a charge and discharge performance diagram of the composite negative electrode material of Example 1 of the present invention.
[0053] Figure 5 Graph showing the cycle performance of the composite negative electrode materials of Example 1 and Comparative Example 1 of the present invention at 10C.
[0054] Figure 6TEM images showing the heterogeneous nucleation point density in Examples 1 and 100-103 of the present invention. DETAILED DESCRIPTION
[0055] The following is a detailed description of the embodiments of the present invention, which are exemplary and are only used to explain the present invention, and should not be construed as limiting the present invention. The term "comprising" and other equivalent descriptions involved in the specification and claims of this application are intended to cover non-exclusive inclusions, including both the contents clearly described in the specification and claims and the steps or units that are not described in the specification and claims but are inherent in the product, method or structure.
[0056] A first aspect of an embodiment of the present invention provides a metal-based composite material, comprising a base material and an active material loaded on the base material; the active material comprises a metal matrix and nano-diamond particles distributed in the metal matrix; the nano-diamond particles comprise a diamond core and an amorphous carbon layer, and the amorphous carbon layer covers at least a portion of the surface of the diamond core.
[0057] The present invention utilizes the amorphous carbon layer on the surface of nano-diamond particles, which can effectively improve the wettability of the interface electrolyte, promote the formation of a uniform and stable solid electrolyte interface (SEI) film, and improve the electrochemical stability of the material; and the diamond core has the characteristics of high hardness and good chemical stability, which inhibits the cracks and structural damage caused by the volume expansion of the material, and effectively improves the structural stability of the composite material. In addition, the present invention significantly increases the electrochemical contact area of the material through the composite structure of nano-diamond particles and metal matrix, and optimizes the transmission path of metal cations. Specifically, the introduction of nano-diamond particles is conducive to the formation of a rich heterogeneous interface, providing a fast metal cation diffusion path, thereby improving the high rate charge and discharge performance of the battery; and the introduction of diamond particles can also induce the heterogeneous nucleation of the metal matrix, inhibit excessive grain growth, effectively deal with the volume expansion and stress gradient caused by the alloying reaction, and improve the overall stability of the structure; and the high thermal conductivity of nano-diamond particles also helps to enhance the heat dissipation capacity and thermal stability of the composite material, reduce the risk of thermal runaway, and ensure the safety and stability of the material under high load or high temperature conditions.
[0058] In some embodiments of the present invention, the average particle size of the nano-diamond particles is 0.5-200 nm; in some specific embodiments of the present invention, the average particle size of the nano-diamond particles is 1-80 nm; in some examples of the present invention, the average particle size of the nano-diamond particles is 1.5-30 nm. Non-limiting specific examples include 1.5 nm, 2 nm, 3 nm, 4 nm, 5 nm, 6 nm, 7 nm, 10 nm, 15 nm, 20 nm, 25 nm, and 30 nm.
[0059] In some embodiments of the present invention, the ratio of the thickness of the amorphous carbon layer to the diameter of the diamond core is 1-40%; in some specific embodiments of the present invention, the ratio of the thickness of the amorphous carbon layer to the diameter of the diamond core is 3-20%; in some examples of the present invention, the ratio of the thickness of the amorphous carbon layer to the diameter of the diamond core is 5-15%. Non-limiting specific examples are 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%.
[0060] In some embodiments of the present invention, the nano-diamond particles are distributed in the metal matrix in a content gradient that gradually decreases from the surface to the interior.
[0061] The design of the nano-diamond particle content gradient of the present invention is not only conducive to improving the wettability of the material with the electrolyte, but also can optimize the mechanical strength and electrochemical properties of the material, effectively reduce stress concentration in the material, enhance the anti-fracture performance of the overall structure, and ensure that the material has good stability and high-rate performance during the battery cycle.
[0062] In some embodiments of the present invention, the content of nano-diamond particles on the surface of the metal matrix is 10-80%; in some specific embodiments of the present invention, the content of nano-diamond particles on the surface of the metal matrix is 50-80%; in some examples of the present invention, the content of nano-diamond particles on the surface of the metal matrix is 50-70%. Non-limiting specific examples include 50%, 52%, 55%, 58%, 60%, 62%, 65%, 68%, and 70%.
[0063] In some embodiments of the present invention, the total content of nano-diamond particles in the metal matrix is 1-50%; in some specific embodiments of the present invention, the total content of nano-diamond particles in the metal matrix is 5-40%; in some examples of the present invention, the total content of nano-diamond particles in the metal matrix is 10-30%. Non-limiting specific examples are 10%, 12%, 15%, 18%, 20%, 22%, 25%, 28%, 30%.
[0064] In some embodiments of the present invention, the thermal conductivity of the nano-diamond particles is 300-3000 W / m·K; in some specific embodiments of the present invention, the thermal conductivity of the nano-diamond particles is 500-2000 W / m·K; in some examples of the present invention, the thermal conductivity of the nano-diamond particles is 700-1200 W / m·K. Non-limiting specific examples include 700 W / m·K, 750 W / m·K, 800 W / m·K, 850 W / m·K, 900 W / m·K, 950 W / m·K, 1000 W / m·K, 1050 W / m·K, 1100 W / m·K, 1150 W / m·K, and 1200 W / m·K.
[0065] In some embodiments of the present invention, nano-diamond particles are prepared by a method comprising the following steps: reacting a nano-diamond raw material with an acid to obtain nano-diamond particles.
[0066] Due to the oxidation effect of acid, the surface carbon atoms of the diamond raw material will be rearranged, thereby generating an amorphous carbon layer structure rich in polar functional groups. This amorphous carbon layer structure rich in polar functional groups can effectively improve the interface wettability between the material and the electrolyte, thereby facilitating the formation of a uniform and stable SEI film.
[0067] In some embodiments of the present invention, in the method for preparing nano-diamond particles, the acid includes sulfuric acid, nitric acid or a combination thereof; in some specific embodiments of the present invention, the acid includes sulfuric acid and nitric acid; in some examples of the present invention, in the acid, the volume ratio of sulfuric acid to nitric acid is 1:(0.5-2); non-limiting specific examples are 1:0.5, 1:1, 1:1.5, 1:2.
[0068] In some embodiments of the present invention, the sulfuric acid is concentrated sulfuric acid, and the nitric acid is concentrated nitric acid.
[0069] In some embodiments of the present invention, in the method for preparing nano-diamond particles, the reaction time of the nano-diamond raw material and the acid is 1 to 20 hours; in some specific embodiments of the present invention, the reaction time of the nano-diamond raw material and the acid is 1.5 to 15 hours; in some examples of the present invention, the reaction time of the nano-diamond raw material and the acid is 2 to 10 hours. Non-limiting specific examples include 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, and 10 hours.
[0070] By adjusting the reaction time of the nanodiamond raw material and the acid, the thickness of the amorphous carbon layer can be adjusted.
[0071] In some embodiments of the present invention, the metal matrix includes at least one metal element of tin, antimony, bismuth, aluminum or zinc; in some specific embodiments of the present invention, the metal matrix includes one metal element of tin, antimony, bismuth, aluminum or zinc.
[0072] The present invention can use different metal materials as the metal matrix, especially tin, antimony, bismuth, aluminum or zinc or their alloys. These metal matrices of different materials can support the performance requirements of different batteries such as sodium-based, lithium-based, calcium-based, potassium-based, zinc-based, etc., and obtain good specific capacity and cycle stability.
[0073] In some embodiments of the present invention, the grain size of the metal matrix presents a gradient structure that gradually decreases from the inside to the surface.
[0074] Due to the introduction of nano-diamond particle phase into the metal matrix, the heterogeneous nucleation of the metal matrix phase is induced, thereby increasing the nucleation density and inhibiting grain growth. In the area with high nano-diamond particle content, the metal matrix phase has a smaller crystal grain size, thereby forming a gradient structure in which the metal matrix grain size gradually refines from the inside to the surface, forming a performance distribution that is strong on the outside and tough on the inside, which can well adapt to the volume expansion and stress gradient caused by the alloying reaction and improve the structural stability.
[0075] In some embodiments of the present invention, the metal matrix contains heterogeneous nucleation sites.
[0076] By introducing second phase nanodiamond particles into the metal matrix, it is beneficial to form abundant heterogeneous nucleation sites, provide fast diffusion channels for ions, and improve the reaction kinetics of the material.
[0077] In some embodiments of the present invention, the density of heterogeneous nucleation sites in the metal matrix is 10 8 ~10 12 Pieces / cm 2 In some specific embodiments of the present invention, the density of heterogeneous nucleation sites in the metal matrix is 5×10 8 ~5×10 11 Pieces / cm 2 In some examples of the present invention, the density of heterogeneous nucleation sites in the metal matrix is 10 9 ~10 11 Pieces / cm 2 . Non-limiting specific examples include 10 9 Pieces / cm 2 , 2×10 9 Pieces / cm 2 , 5×10 9 Pieces / cm 2 , 8×10 9 Pieces / cm 2 , 10 10 Pieces / cm 2 , 2×10 10 Pieces / cm 2 , 5×10 10 Pieces / cm 2 , 8×10 10 Pieces / cm 2 , 10 11 Pieces / cm 2 .
[0078] In some embodiments of the present invention, the substrate material includes a porous material or a non-porous material; in some specific embodiments of the present invention, the substrate material is selected from porous materials.
[0079] In some embodiments of the present invention, the porous material is prepared by a method comprising the following steps: electrochemically etching a non-porous material of the same material, wherein the current density used in the electrochemical etching is 10 to 30 mA / cm 2 , and a porous material is obtained.
[0080] In some specific embodiments of the present invention, the current density used for electrochemical etching is 15-25 mA / cm 2 ; Non-limiting specific examples such as 15mA / cm 2 , 18mA / cm 2 , 20mA / cm 2 , 22mA / cm 2 or 25mA / cm 2 .
[0081] In some specific embodiments of the present invention, the etching time of the electrochemical etching is 15 to 35 minutes; non-limiting specific examples are 15 minutes, 20 minutes, 25 minutes, 30 minutes or 35 minutes.
[0082] In some specific embodiments of the present invention, the etching solution used in electrochemical etching is an acidic solution; in some examples of the present invention, the acidic solution includes at least one of a hydrochloric acid solution, a sulfuric acid solution or a nitric acid solution; in some examples of the present invention, the acidic solution is selected from a hydrochloric acid solution.
[0083] In some specific embodiments of the present invention, the concentration of the acidic solution is 5 to 10 mol / L; non-limiting specific examples are 5 mol / L, 6 mol / L, 7 mol / L, 8 mol / L, 9 mol / L or 10 mol / L.
[0084] In some embodiments of the present invention, the porous material includes at least one of porous aluminum, porous copper, porous nickel or porous stainless steel; in some specific embodiments of the present invention, the porous material is selected from porous aluminum.
[0085] Compared with other porous materials, porous aluminum may have higher porosity, better pore structure distribution and material conductivity after electrochemical etching. In addition, the pore structure of porous aluminum is more uniform and more conducive to the penetration of electrolyte. These characteristics together improve its ion transfer efficiency and electrode stability.
[0086] In some embodiments of the present invention, the non-porous material includes at least one of aluminum foil, copper foil, titanium foil, stainless steel foil, platinum foil, zinc foil, gold foil, nickel mesh, tungsten mesh, graphene film, carbon cloth or carbon paper.
[0087] In some embodiments of the present invention, the porous aluminum is prepared by a method comprising the following steps: electrochemically etching the aluminum foil in a hydrochloric acid solution; the current density is 10 to 30 mA / cm2 , the etching time is 20 to 30 minutes; in some specific embodiments of the present invention, the concentration of the hydrochloric acid solution is 5 to 10 mol / L.
[0088] The second aspect of an embodiment of the present invention provides a method for preparing a metal-based composite material according to the first aspect of an embodiment of the present invention, comprising the following steps: using a solution containing a metal salt and nano-diamond particles as a plating solution and a base material as an electrode to perform electroplating to obtain a metal-based composite material; the metal elements in the metal salt include the metal elements in the metal matrix.
[0089] The preparation method provided by the present invention has a simple process and low cost, and can produce a metal-based composite material with excellent electrochemical performance and wettability, and has good application prospects in the preparation of high-performance electrode materials and batteries.
[0090] In some embodiments of the present invention, the current density of the electroplating process is 1-30 mA / cm 2 In some specific embodiments of the present invention, the current density of the electroplating process is 7 to 18 mA / cm 2 In some examples of the present invention, the current density of the electroplating process is 9 to 12 mA / cm 2 . Non-limiting specific examples include 9mA / cm 2 , 9.5mA / cm 2 , 10mA / cm 2 , 10.5mA / cm 2 , 11mA / cm 2 , 11.5mA / cm 2 , 12mA / cm 2 .
[0091] In some embodiments of the present invention, the deposition time of the electroplating process is 5 to 40 minutes; in some specific embodiments of the present invention, the deposition time of the electroplating process is 15 to 30 minutes; in some examples of the present invention, the deposition time of the electroplating process is 18 to 22 minutes. Non-limiting specific examples include 18 minutes, 18.5 minutes, 19 minutes, 19.5 minutes, 20 minutes, 20.5 minutes, 21 minutes, 21.5 minutes, and 22 minutes.
[0092] In some embodiments of the present invention, the plating solution further contains gelatin.
[0093] Gelatin is added to the plating solution, which can act as a stabilizer and binder, effectively controlling the co-deposition process of nanodiamond and tin, avoiding excessive aggregation, and ensuring the uniform distribution of the metal matrix and a good electrode structure.
[0094] In some specific embodiments of the present invention, the mass content of gelatin in the plating solution is 0.1-5%; in some specific embodiments of the present invention, the mass content of gelatin in the plating solution is 0.3-3%; in some examples of the present invention, the mass content of gelatin in the plating solution is 0.5-2%. Non-limiting specific examples include 0.5%, 0.8%, 1%, 1.2%, 1.5%, 1.8%, and 2%.
[0095] A third aspect of the embodiments of the present invention provides a negative electrode material, comprising the metal-based composite material of the first aspect of the embodiments of the present invention, or the metal-based composite material prepared by the preparation method of the second aspect of the embodiments of the present invention.
[0096] The metal-based composite material provided in the embodiments of the present invention has good comprehensive properties such as structural stability, cycle performance, high-rate charge and discharge performance and safety performance, and can be used to prepare negative electrode materials with excellent electrochemical properties.
[0097] In some embodiments of the present invention, the negative electrode material does not include a conductive agent and a binder.
[0098] The negative electrode material provided in the embodiment of the present invention has good structural stability and conductivity, and good electrochemical performance and energy density can be obtained without adding additional conductive agents and binders.
[0099] A fourth aspect of the embodiments of the present invention provides a battery, comprising a positive electrode material, an electrolyte, and the negative electrode material of the third aspect of the embodiments of the present invention.
[0100] The battery made by using the negative electrode material in the embodiment of the present invention has good structural stability and electrochemical performance, especially has excellent specific capacity and cycle performance.
[0101] In some embodiments of the present invention, the positive electrode material includes graphite, sodium cobalt oxide (e.g., NaCoO 2 ), sodium nickel manganese oxide (e.g. NaNi 0.5 Mn 0.5 O 2 ), sodium nickel sulfide (such as Na 3 Ni 2 SbO 6 ), sodium manganese oxides (such as NaMnO 2 ), sodium iron phosphate (e.g. NaFePO 4 ), sodium nickel ferrocyanide (e.g. sodium nickel [hexacyanoferrate (II)] Na 2 NiFe(CN) 6 ), vanadium-based oxides (e.g. NaVO 3 ) or sodium ferric fluoride (e.g. NaFeF 3) at least one; in some specific embodiments of the present invention, the positive electrode material is selected from graphite; in some examples of the present invention, the positive electrode material is selected from expanded graphite.
[0102] Using expanded graphite as the positive electrode material has excellent cycle stability and is suitable for long-term applications.
[0103] In some embodiments of the present invention, the battery includes at least one of a sodium ion battery, a lithium ion battery, a calcium ion battery, a potassium ion battery, or a zinc ion battery.
[0104] The content of the present invention is further described in detail below through specific examples. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the principles set forth in the present invention all belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are also only examples within a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not limited to the specific data exemplified below. The raw materials, reagents or devices used in the following examples, unless otherwise specified, can all be obtained from conventional commercial sources, or can be obtained by existing known methods.
[0105] Example 1
[0106] This embodiment provides a tin-based composite negative electrode material (PAL-Sn@ND), the structure of which is shown in FIG. Figure 1 As shown, it includes porous aluminum and a tin@nano-diamond active functional layer loaded on the porous aluminum; the tin@nano-diamond active functional layer includes a tin matrix and nano-diamond particles distributed in the tin matrix. The TEM image of the nano-diamond particles in this example is shown in Figure 2 As shown, (a) is a zoomed-out view, (b) and (c) are magnified views, and (c) also marks the position and thickness (1 nm) of the amorphous carbon layer. Figure 2 It can be seen that the nano-diamond particles include a diamond core and an amorphous carbon layer, and the amorphous carbon layer covers at least a portion of the surface of the diamond core.
[0107] The tin-based composite negative electrode material (PAL-Sn@ND) in this example is prepared by preparing a tin@nano-diamond composite active functional layer on porous aluminum by a nano-composite electroplating method. The specific preparation method is as follows:
[0108] S1. Preparation of nano-diamond suspension: Weigh an appropriate amount of nano-diamond raw material powder with an average particle size of 10nm and place it in a reactor. Pour concentrated nitric acid and concentrated sulfuric acid into the reactor in a volume ratio of 1:1, add a magnetic stirrer at 450-500rpm, and react for 3h; after the reaction, take a sample into a centrifuge tube and centrifuge at 5000rpm for 10min. After the centrifugation, pour out the supernatant and add an appropriate amount of deionized water. Repeat the above operation 3-5 times, collect the centrifuged product; then add an appropriate amount of water-soluble emulsifying dispersant sodium dodecylbenzene sulfonate, and ultrasonically disperse for 30min to obtain a uniformly dispersed nano-diamond suspension.
[0109] S2, preparation of plating solution: stannous sulfate, potassium pyrophosphate decahydrate and gelatin are mixed in an electroplating tank, and the nano-diamond suspension prepared in step S1 is added, and ultrasonic stirring is performed until uniform to obtain a plating solution. Among them, the mass ratio of stannous sulfate to potassium pyrophosphate decahydrate is 2:8, the mass content of gelatin in the plating solution is 1%, and the mass content of nano-diamond in the plating solution is 1%.
[0110] S3. Preparation of porous aluminum: take an aluminum foil with a purity of ≥99.9% and a thickness of 50 μm, wash it with a sodium hydroxide solution with a mass fraction of 1% to remove the surface oxide film; put the aluminum foil into a hydrochloric acid solution with a concentration of 8 mol / L, connect the current for electrochemical etching, and the current density is 20 mA / cm 2 , etching time 25min; immerse the etched porous aluminum foil in ethanol and deionized water in sequence and ultrasonically wash for 2min, repeat 2-3 times, and vacuum dry at 50℃ for 5h.
[0111] S4. Preparation of Sn@Nanodiamond active functional layer: Place the treated porous aluminum cathode and tin foil anode in an electroplating tank and connect the circuit for nanocomposite co-plating at a current density of 10 mA / cm 2 After the electroplating is completed, the prepared electrode is placed in acetone, ethanol, and deionized water in sequence and immersed in ultrasonic washing for 2 minutes, repeated 2-3 times, and vacuum dried at 50°C for 12 hours to obtain a PAL-Sn@ND composite negative electrode material with a tin@nanodiamond active functional layer.
[0112] Pole preparation, battery assembly and testing:
[0113] The vacuum-dried composite negative electrode material electrode sheet is cut into pieces of suitable size and collected in the glove box for later use. Preparation of battery graphite positive electrode: Expanded graphite, conductive carbon black, and polytetrafluoroethylene are weighed in a grinding device at a mass ratio of 8:1:1, and then N-methylpyrrolidone solvent is added to grind thoroughly to obtain a uniform slurry; then the slurry is evenly coated on the surface of the aluminum foil, and the surface density of the electrode is controlled to be 10mg / cm 2, vacuum dried at 80℃ for 12h, cut the dried electrode sheets into pieces of suitable size, weigh them and place them in the glove box for later use. Preparation of diaphragm: cut the glass fiber paper into pieces of suitable size, dry them in a drying oven and place them in the glove box for later use as diaphragm. Preparation of electrolyte: weigh 2M NaPF 6 Add to 10mL of mixed solvent of ethyl methyl carbonate (EMC), ethylene carbonate (EC), and dimethyl carbonate (DMC) (volume ratio = 3:2:2) and stir until NaPF 6 Completely dissolved to make 2MNaPF 6 / (ethyl methyl carbonate (EMC), ethylene carbonate (EC), dimethyl carbonate (DMC)) solution is used as an electrolyte for standby use. Assembling the battery: In an argon-protected glove box, the prepared battery negative electrode, separator and battery positive electrode are stacked in sequence, and then an appropriate amount of electrolyte is added, and the battery is encapsulated in a battery casing to complete the battery assembly and obtain a secondary battery.
[0114] The electrochemical performance of the prepared secondary battery was tested using the NEWARE battery testing system; and the electrolyte was dripped onto the vacuum-dried composite negative electrode material electrode sheet to test the wetting performance of the composite negative electrode material and the electrolyte.
[0115] Comparative Example 1
[0116] Comparative Example 1 provides a tin-based composite negative electrode material (PAL-Sn), which is different from Example 1 in that the active functional layer is only tin. The preparation method of this example is different from that of Example 1 in that this example does not include step S1, and the plating solution of step S2 does not include a nano-diamond suspension. The other preparation steps are the same as those of Example 1, and tin is electrochemically deposited on porous aluminum alone. The electrochemical performance and wetting performance of Comparative Example 1 were tested using the method in Example 1.
[0117] Figure 3 The wettability diagram of the composite negative electrode material and the electrolyte of Example 1 and Comparative Example 1, wherein (a) is Comparative Example 1, and (b) is Example 1; Figure 3 It can be seen that the PAL-Sn@ND tin-based composite negative electrode material electrode sheet prepared in Example 1 has better wettability with the electrolyte.
[0118] Figure 4 This is a charge and discharge performance diagram of the composite negative electrode material of Example 1; Figure 5 The cycle performance diagram of the composite negative electrode material of Example 1 and Comparative Example 1 at 10C. Figure 4 It can be seen that the composite negative electrode material of Example 1 has good charge and discharge performance; Figure 5It can be seen that after the composite modification of nano-diamond and tin nano-composite electroplating in Example 1, the porous aluminum-tin@nano-diamond composite negative electrode material obtained has higher cycle stability. Using a high-rate cycle of 10C (5mA / g), the capacity retention rate reaches 80% when the cycle is cycled to 5100 cycles; compared with the porous aluminum-tin composite negative electrode material obtained in Comparative Example 1 (the capacity retention rate is 80% after 600 cycles), it is increased by 850%.
[0119] Example 2-16
[0120] Examples 2-16 each provide a tin-based composite negative electrode material (different substrate - Sn@ND). The difference from Example 1 is that Examples 2-16 use different substrate materials to replace the porous aluminum substrate. The specific substrate materials are shown in Table 1; the other preparation steps and raw materials are the same as Example 1.
[0121] The electrochemical properties of Examples 2-16 were tested using the method in Example 1 and compared with the performance of Example 1 of the present invention. The electrochemical properties of the substrate types and materials used in Examples 1-16 are shown in Table 1 below.
[0122] Table 1 Substrate types and electrochemical properties of materials used in Examples 1-16
[0123]
[0124]
[0125] As can be seen from Table 1, the battery using porous aluminum as the substrate in Example 1 performs best in both specific capacity and number of cycles. This may be attributed to the fact that the porous aluminum structure can provide a larger surface area and more active sites, which promotes the penetration of electrolyte and the transmission efficiency of ions. At the same time, the good conductivity and mechanical stability of porous aluminum also help to maintain the integrity and electrochemical activity of the electrode structure, thereby significantly improving the cycle stability and service life of the battery. These characteristics make porous aluminum an ideal choice for making high-performance secondary battery negative electrodes.
[0126] Examples 17-27
[0127] Examples 17-27 each provide a tin-based composite negative electrode material (PAL-Sn@ND). The difference from Example 1 is that the average particle size of the nanodiamonds in Examples 17-27 is different. The specific average particle size of the nanodiamonds is shown in Table 2; the other preparation steps and raw materials are the same as those in Example 1.
[0128] The electrochemical properties of Examples 17-27 were tested using the method in Example 1 and compared with the performance of Example 1 of the present invention. The electrochemical properties of the nanodiamond particle sizes and materials used in Examples 1 and 17-27 are shown in Table 2 below.
[0129] Table 2 Average particle size of nanodiamonds and electrochemical properties of materials in Examples 1, 17-27
[0130]
[0131]
[0132] As can be seen from Table 2, the particle size of nanodiamond has a significant effect on the electrochemical performance of the PAL-Sn@ND composite negative electrode material. The best performance occurs when nanodiamonds with a particle size of about 10nm are used, at which the specific capacity and number of cycles are the highest. As the particle size increases, the specific capacity decreases slightly, especially when the particle size exceeds 40nm, the number of cycles decreases significantly, indicating that nanodiamonds with larger particle sizes may lead to inhomogeneity of the electrode structure and reduced electrochemical activity. This shows that smaller nanodiamond particle sizes are more conducive to improving the structural stability and electrochemical performance of the electrode.
[0133] Examples 28-34
[0134] Examples 28-34 each provide a tin-based composite negative electrode material (PAL-Sn@ND). The difference from Example 1 is that the ratio of the thickness of the amorphous carbon layer to the diameter of the diamond core in Examples 28-34 is different (the thickness of the amorphous carbon layer is mainly adjusted by adjusting the reaction time of the diamond and the acid in step S1, and the thickness of the amorphous carbon layer is obtained by TEM testing), and the specific ratio is shown in Table 3; the other preparation steps and raw materials are the same as those in Example 1.
[0135] The electrochemical properties of Examples 28-34 were tested using the method in Example 1 and compared with the performance of Example 1 of the present invention. The ratio of the amorphous carbon layer thickness to the diamond core diameter and the electrochemical properties of the materials of Example 1 and Examples 28-34 are shown in Table 3 below.
[0136] Table 3 Ratio of amorphous carbon layer thickness to diamond core diameter and electrochemical properties of materials in Examples 1, 28-34
[0137]
[0138] As can be seen from Table 3, the ratio of the thickness of the amorphous carbon layer on the surface of the nanodiamond particles to the diameter of the diamond core has a significant effect on the electrochemical performance of the battery. The 10% ratio used in Example 1 performed best, with the highest specific capacity and number of cycles. When the ratio is lower or higher than 10%, the cycle stability and specific capacity of the battery generally show a downward trend, especially when the ratio reaches 50%, the performance is significantly reduced. This shows that a moderate amorphous carbon layer thickness helps to optimize the contact of the electrolyte and the transport of ions, thereby improving battery performance. Too thin or too thick a carbon layer may hinder these processes.
[0139] Examples 35-41
[0140] Examples 35-41 each provide a tin-based composite negative electrode material (PAL-Sn@ND), which differs from Example 1 in that the surface nanodiamond content of the negative electrode materials of Examples 35-41 is different (the surface nanodiamond content is mainly adjusted by adjusting the amount of nanodiamond suspension added in step S2, and the surface nanodiamond content is obtained by measuring the carbon content on the sample surface by energy dispersive X-ray spectroscopy EDS), and the specific content is shown in Table 4; the other preparation steps and raw materials are the same as those in Example 1.
[0141] The electrochemical properties and wetting properties of Examples 35-41 were tested using the method in Example 1 and compared with the performance of Example 1 of the present invention. The surface nanodiamond content, electrochemical properties and contact angles of the materials of Example 1 and Examples 35-41 are shown in Table 4 below.
[0142] Table 4 Surface nanodiamond content and electrochemical properties and contact angles of Examples 1, 35-41
[0143]
[0144] As can be seen from Table 4, the surface nanodiamond content has a significant effect on the electrochemical properties of the PAL-Sn@ND composite negative electrode material. When the content is 60% (Example 1), the specific capacity and number of cycles are the highest, the contact angle is the smallest, and the interface wettability is good. As the content decreases, the contact angle increases, the wettability deteriorates, and the specific capacity and number of cycles decrease (Examples 35-38). When the content increases to 50%-80% (Examples 39-41), the contact angle decreases significantly, the wettability improves, and the electrochemical performance is restored, especially at 50%-70%, which shows better cycle performance. In summary, a nanodiamond content of 60% can achieve the best electrochemical performance and interface characteristics.
[0145] Examples 42-46
[0146] Examples 42-46 each provide a tin-based composite negative electrode material (PAL-Sn@ND). The difference from Example 1 is that the distribution concentration of the nanodiamonds in Examples 42-46 in the metal matrix is different (the distribution concentration is mainly adjusted by adjusting the amount of nanodiamond suspension added in step S2), and the specific distribution concentration is shown in Table 5; the other preparation steps and raw materials are the same as those in Example 1.
[0147] The electrochemical properties of Examples 42-46 were tested using the method in Example 1 and compared with the performance of Example 1 of the present invention. The distribution concentration of nanodiamonds in the metal matrix and the electrochemical properties of the materials of Example 1 and Examples 42-46 are shown in Table 5 below.
[0148] Table 5 Distribution concentration of nanodiamonds in metal matrix and electrochemical properties of materials of Examples 1, 42-46
[0149]
[0150] As can be seen from Table 5, the distribution concentration of nanodiamonds in the metal matrix has a significant effect on the electrochemical properties of the PAL-Sn@ND composite negative electrode material. When the concentration is 20% (Example 1), the specific capacity and the number of cycles reach the highest values, which are 95mAh / g and 5100 times, respectively. As the concentration decreases (Examples 42-43), the specific capacity and the number of cycles decrease, but when the concentration is 10% (Example 43), the number of cycles increases to 4122 times, indicating that it has good cycle performance at this concentration. As the concentration increases (Examples 44-46), the specific capacity reaches 90mAh / g at 30%, but the number of cycles decreases slightly. At high concentrations (40%-50%), the electrochemical performance decreases, indicating that excessively high nanodiamond concentrations may lead to reduced electrode performance.
[0151] Examples 47-51
[0152] Examples 47-51 each provide a tin-based composite negative electrode material (PAL-Sn@ND). The difference from Example 1 is that the thermal conductivity of the nanodiamonds in Examples 47-51 is different (the thermal conductivity is mainly adjusted by adjusting the amount of nanodiamonds), and the specific thermal conductivity is shown in Table 6; the other preparation steps and raw materials are the same as those in Example 1.
[0153] The electrochemical properties of Examples 47-51 were tested using the method in Example 1 and compared with the performance of Example 1 of the present invention. The thermal conductivity of the nanodiamonds and the electrochemical properties of the materials of Example 1 and Examples 47-51 are shown in Table 6 below.
[0154] Table 6 Thermal conductivity of nanodiamonds and electrochemical properties of materials in Examples 1, 47-51
[0155] Example No. Thermal conductivity of nanodiamond (W / m·K) Specific capacity (mAh / g) Cycle times (times) 1 1000 95 5100 47 500 94 4402 48 700 92 4680 49 1200 93 4698 50 1500 93 4005 51 2000 94 4578
[0156] As can be seen from Table 6, the thermal conductivity of nanodiamond has a significant effect on the electrochemical properties of the PAL-Sn@ND composite negative electrode material. When the thermal conductivity is 1000W / m·K (Example 1), the specific capacity and the number of cycles are 95mAh / g and 5100 times, respectively. When the thermal conductivity is reduced to 500W / m·K (Example 47), the specific capacity is slightly reduced to 94mAh / g, and the number of cycles is reduced to 4402 times. When the thermal conductivity is in the range of 700-1200W / m·K (Examples 48-49), the number of cycles is relatively high, 4680 times and 4698 times, respectively, but the specific capacity is relatively low, about 92-93mAh / g. When the thermal conductivity is further increased to 1500-2000W / m·K (Examples 50-51), the specific capacity and the number of cycles are reduced, indicating that excessive thermal conductivity may affect electrode performance. In general, when the thermal conductivity is in the range of 700-1200 W / m·K, the material exhibits better cycle performance.
[0157] Examples 52-56
[0158] Examples 52-56 each provide a tin-based composite negative electrode material (PAL-Sn@ND). The difference from Example 1 is that the gelatin content in the plating solution of step S2 of Examples 52-56 is different, and the specific gelatin content is shown in Table 7; the other preparation steps and raw materials are the same as Example 1.
[0159] The electrochemical properties of Examples 52-56 were tested using the method in Example 1 and compared with the performance of Example 1 of the present invention. The gelatin content in the plating solution of Example 1 and Examples 52-56 and the electrochemical properties of the materials are shown in Table 7 below.
[0160] Table 7 Gelatin content in the plating solution of Examples 1, 52-56 and electrochemical properties of the materials
[0161] Example No. Gelatin content in plating solution (%) Specific capacity (mAh / g) Cycle times (times) 1 1 95 5100 52 0 89 3000 53 0.5 92 4290 54 1.5 90 4350 55 3 88 3730 56 5 90 2220
[0162] It can be seen from Table 7 that the gelatin content in the plating solution has a significant effect on the electrochemical properties of the PAL-Sn@ND composite negative electrode material. The ratio of 1% gelatin used in Example 1 shows the best performance. This may be because the appropriate gelatin content helps to optimize the microstructure and surface properties of the electrode material, and improve its uniformity and adhesion. Gelatin acts as a stabilizer and binder in the plating solution, which can effectively control the co-deposition process of nanodiamonds and tin, avoid excessive aggregation, and ensure the uniform distribution of tin and a good electrode structure. A moderate gelatin content (1%) not only ensures the integrity of the deposited layer, but also maintains good electrical conductivity and ion transport channels, thereby achieving a higher specific capacity and excellent cycle stability.
[0163] Examples 57-67
[0164] Examples 57-67 each provide a tin-based composite negative electrode material (PAL-Sn@ND). The difference from Example 1 is that the current density in step S4 of Examples 57-67 is different, and the specific current density is shown in Table 8; the other preparation steps and raw materials are the same as those in Example 1.
[0165] The electrochemical properties of Examples 57-67 were tested using the method in Example 1 and compared with the performance of Example 1 of the present invention. The current density and electrochemical properties of the materials of Example 1 and Examples 57-67 are shown in Table 8 below.
[0166] Table 8 Current density and electrochemical properties of materials in Examples 1, 57-67
[0167] Example No. <![CDATA[Current density (mA / cm 2 )]]> Specific capacity (mAh / g) Cycle times (times) 1 10 95 5100 57 1 102 484 58 2 106 496 59 4 98 927 60 6 100 1422 61 9 94 3468 62 12 97 3932 63 15 90 2021 64 18 93 2083 65 21 89 1843 66 25 91 1719 67 30 90 1519
[0168] It can be seen from Table 8 that the current density has a significant effect on the electrochemical performance of the PAL-Sn@ND tin composite negative electrode material prepared by nanocomposite electroplating. 2 ) can provide high specific capacity, but the number of cycles is low, reflecting that the electrode structure may be loose or uneven. As the current density increases to the medium range (9-12mA / cm 2 ), the cycling stability of the electrode was significantly improved, indicating that at this current density, the deposition process is more conducive to the formation of a stable and uniform electrode structure. However, when the current density is further increased (more than 15 mA / cm 2 ), the specific capacity and cycle number decreased, which may be due to the increased stress and rapid degradation of the electrode material caused by the excessively high current density.
[0169] From the microstructure point of view, the PAL-Sn@ND tin-based composite negative electrode materials deposited at different current densities show significant differences. 2 ) the electrode structure is loose and the porosity is large, resulting in poor cycle stability; at medium current density (9-12 mA / cm 2 ) the surface morphology of the material is more uniform and dense, the grain size is effectively controlled, the porosity is moderate, and a stable electrolyte infiltration channel is formed; while at high current density (≥15mA / cm 2 ), the stress concentration phenomenon in the material is obvious, the surface cracks increase, and the electrode degrades rapidly. This shows that the current density has a direct impact on the electrode structure characteristics, and the electrode structure characteristics can be adjusted by regulating the current density.
[0170] Examples 68-78
[0171] Examples 68-78 each provide a tin-based composite negative electrode material (PAL-Sn@ND). The difference from Example 1 is that the electroplating deposition time in step S4 of Examples 68-78 is different, and the specific electroplating deposition time is shown in Table 9; the other preparation steps and raw materials are the same as those in Example 1.
[0172] The electrochemical properties of Examples 68-78 were tested using the method in Example 1 and compared with the performance of Example 1 of the present invention. The electroplating deposition time and electrochemical properties of the materials of Example 1 and Examples 68-78 are shown in Table 9 below.
[0173] Table 9 Electroplating deposition time and electrochemical properties of materials in Examples 1, 68-78
[0174] Example No. Electroplating deposition time (min) Specific capacity (mAh / g) Cycle times (times) 1 20 95 5100 68 5 104 544 69 7 98 536 70 9 101 848 71 12 99 1342 72 15 94 2168 73 18 97 2934 74 22 89 2422 75 25 93 2047 76 30 88 1903 77 35 102 1638 78 40 94 1647
[0175] It can be seen from Table 9 that the electroplating deposition time has a significant effect on the electrochemical properties of the PAL-Sn@ND composite negative electrode material. Shorter electroplating deposition times (such as 5-9 minutes) provide higher specific capacity, but lower cycle times, indicating that the electrode may be weaker or uneven. With the increase of electroplating deposition time, the cycle stability of the electrode gradually improves, indicating that longer electroplating deposition time is conducive to the formation of a more uniform and structurally stable electrode layer. However, when the electroplating deposition time is too long (more than 22 minutes), the specific capacity begins to decrease, which may be due to the increase in internal resistance caused by the excessive thickness of the electrode, affecting the battery performance. The optimal electroplating deposition time is between 18 and 22 minutes, which can achieve better overall performance.
[0176] Examples 79-91
[0177] Examples 79-91 each provide a metal-based composite negative electrode material (PAL-M@ND, M is tin, antimony, bismuth, aluminum, zinc). The difference from Example 1 is that different metal salt plating solutions are used in step S2 of Examples 79-91 to prepare negative electrodes containing different main phase metals I, and to assemble into different types of batteries. The specific main phase metals I and battery types are shown in Table 10; other preparation steps and raw materials are the same as those in Example 1.
[0178] The electrochemical properties of Examples 79-91 were tested using the method in Example 1 and compared with the performance of Example 1 of the present invention. The electrochemical properties of the main phase metal I, battery types and materials of Example 1 and Examples 79-91 are shown in Table 10 below.
[0179] Table 10 Main phase metal I, battery type and electrochemical properties of materials in Examples 1, 79-91
[0180] Example No. Main phase metal Ⅰ Battery Type Specific capacity (mAh / g) Cycle times (times) 1 tin Sodium-based dual-ion battery 95 5100 79 tin Lithium-based dual-ion battery 98 5050 80 tin Potassium-based dual-ion battery 92 3800 81 tin Calcium-based dual-ion battery 88 2000 82 antimony Lithium-based dual-ion battery 89 3500 83 antimony Sodium-based dual-ion battery 95 4500 84 antimony Potassium-based dual-ion battery 90 3700 85 antimony Calcium-based dual-ion battery 87 1760 86 bismuth Lithium-based dual-ion battery 96 4800 87 bismuth Sodium-based dual-ion battery 85 4920 88 bismuth Potassium-based dual-ion battery 90 3000 89 bismuth Calcium-based dual-ion battery 86 1500 90 aluminum Lithium-based dual-ion battery 90 2000 91 Zinc Zinc-based dual-ion battery 110 2850
[0181] As can be seen from Table 10, by changing the type of main phase metal I, the composite negative electrode material of the present invention shows adaptability and flexibility for different electrochemical systems (sodium-based, lithium-based, calcium-based, potassium-based, zinc-based). Each metal element (tin, antimony, bismuth, aluminum, zinc) not only supports the performance requirements of a specific battery type, but also optimizes specific properties such as specific capacity and cycle stability. This allows the material to be customized according to application requirements, providing the versatility and wide range of applications required when designing battery materials.
[0182] Examples 92-99
[0183] Examples 92-99 each provide a rocking-chair-type sodium-ion battery. The difference from Example 1 is that Examples 92-99 assemble the prepared tin-based composite negative electrode material (PAL-Sn@ND) with different positive electrode materials into a rocking-chair-type sodium-ion battery. The specific types of positive electrode materials are shown in Table 11; and the preparation steps and raw materials of the tin-based composite negative electrode material are the same as those in Example 1.
[0184] The electrochemical properties of Examples 92-99 were tested using the method in Example 1 and compared with the performance of Example 1 of the present invention. The types of positive electrode materials and the electrochemical properties of the materials of Example 1 and Examples 92-99 are shown in Table 11 below.
[0185] Table 11 Types of positive electrode materials and electrochemical properties of materials in Examples 1, 92-99
[0186] Example No. Cathode material type Specific capacity (mAh / g) Cycle times (times) 1 Expanded graphite (C) 95 5100 92 <![CDATA[Sodium cobalt oxide (NaCoO 2 )]]> 190 420 93 <![CDATA[Sodium nickel manganese oxide (NaNi 0.5 Mn 0.5 O 2 )]]> 160 540 94 <![CDATA[Sodium nickel sulfide (Na 3 Ni 2 SbO 6 )]]> 120 335 95 <![CDATA[Sodium manganese oxide (NaMnO 2 )]]> 150 325 96 <![CDATA[Sodium iron phosphate (NaFePO 4 )]]> 120 1200 97 <![CDATA[Sodium nickel hexacyanoferrate(II) (Na 2 NiFe(CN) 6 )]]> 110 500 98 <![CDATA[Vanadium-based oxide (NaVO 3 )]]> 250 200 99 <![CDATA[Sodium iron fluoride (NaFeF 3 )]]> 170 350
[0187] As can be seen from Table 11, Example 1, as a sodium-based dual-ion battery, uses expanded graphite as the positive electrode material, showing excellent cycle stability and is suitable for long-term applications. In contrast, the traditional sodium-ion batteries in Examples 92-99 use a variety of positive electrode materials, which show potential in capacity but have a short cycle life, showing that the long-term stability and durability of the battery may be sacrificed while pursuing high energy density. This comparison emphasizes the importance of balancing performance and application requirements when selecting battery types and materials.
[0188] Examples 100-103
[0189] Examples 100-103 each provide a tin-based composite negative electrode material (PAL-Sn@ND), which is different from Example 1 in that the density of heterogeneous nucleation points in the negative electrode materials of Examples 100-103 is different (by adjusting the electroplating parameters in step S4, such as electric field strength, time, temperature, etc.; the density of heterogeneous nucleation points is directly observed by characterization methods such as thermogravimetry TGA or transmission electron microscopy TEM); the other preparation steps and raw materials are the same as Example 1.
[0190] The electrochemical properties of Examples 100-103 were tested using the method in Example 1 and compared with the performance of Example 1 of the present invention. The heterogeneous nucleation point density and electrochemical properties of the materials of Example 1 and Examples 100-103 are shown in Table 12 below.
[0191] Table 12 Heterogeneous nucleation point density and electrochemical properties of materials in Examples 1, 100-103
[0192]
[0193]
[0194] The data in Table 12 show that the density of heterogeneous nucleation sites has a significant effect on the cycle stability of PAL-Sn@ND composite anode materials. The specific capacity remains basically stable (93-95 mAh / g), but the number of cycles is reduced when the density of heterogeneous nucleation sites is 10 10 Pieces / cm 2 The best performance was achieved at 5100 cycles. 8 Pieces / cm 2 ) or too high (10 12 Pieces / cm 2 ) will reduce the cycle performance, which may be related to the distribution uniformity of grains and the rate of side reactions. Therefore, optimizing the density of heterogeneous nucleation sites is an important design strategy to improve battery performance.
[0195] Figure 6 TEM images of heterogeneous nucleation point density in Examples 1 and 100-103, wherein (a) is Example 103, and the heterogeneous nucleation point density is 10 12 Pieces / cm 2 ; (b) is Example 102, the heterogeneous nucleation point density is 10 11 Pieces / cm 2 ; (c) is Example 1, the heterogeneous nucleation point density is 10 10 Pieces / cm 2 ; (d) is Example 101, the heterogeneous nucleation point density is 10 9 Pieces / cm 2 ; (e) is Example 100, the heterogeneous nucleation point density is 10 8 Pieces / cm 2 .from Figure 6 It can be seen that by controlling different electroplating parameters, negative electrode materials containing different numbers of heterogeneous nucleation sites can be obtained, thereby optimizing the performance of electrodes and batteries.
[0196] The negative electrode material provided in the embodiment of the present invention has a gradually decreasing content of nano-diamond particles from the surface to the inside, and the particles have a double-layer structure, with a diamond core inside and an amorphous carbon layer outside. The main purpose of this structural design is to improve the wettability of the interfacial electrolyte by utilizing the polar functional groups rich in the amorphous carbon layer, promote the formation of a uniform and stable solid electrolyte interface (SEI) film, and improve the electrochemical stability of the electrode. In addition, the introduction of nano-diamonds can also induce heterogeneous nucleation of the metal phase, inhibit excessive grain growth, thereby forming a grain size that is gradually refined from the inside to the surface, effectively responding to the volume expansion and stress gradient caused by the alloying reaction, and improving the overall stability of the structure. Ultimately, this design not only improves the reaction kinetics of the negative electrode material, but also enhances the heat dissipation capacity through the high thermal conductivity of nano-diamonds, reduces the risk of thermal runaway, and thus significantly improves the overall performance and safety of the battery.
[0197] In summary, the present invention utilizes nano-diamond particles containing an amorphous carbon layer and a diamond core, which can effectively improve the wettability of the interface electrolyte, enhance the structural stability of the material, inhibit cracks and structural damage caused by the volume expansion of the material, effectively enhance the structural stability of the composite material, and optimize the transmission path of the metal cations, thereby enhancing the cycle performance and high-rate charge and discharge performance of the material.
Claims
1. A metal matrix composite material, characterized in that: It comprises a base material and an active material loaded on the base material; the active material comprises a metal matrix and nano-diamond particles distributed in the metal matrix; the nano-diamond particles comprise a diamond core and an amorphous carbon layer, and the amorphous carbon layer covers at least a part of the surface of the diamond core.
2. The metal matrix composite material according to claim 1, characterized in that: The average particle size of the nano diamond particles is 0.5-200 nm.
3. The metal matrix composite material according to claim 1, characterized in that: The ratio of the thickness of the amorphous carbon layer to the diameter of the diamond core is 1 to 40%.
4. The metal matrix composite material according to claim 1, characterized in that: The nano-diamond particles are distributed in the metal matrix according to a content gradient that gradually decreases from the surface to the inside.
5. The metal matrix composite material according to claim 4, characterized in that: The content of nano-diamond particles on the surface of the metal substrate is 10-80%; And / or, the total content of nano-diamond particles in the metal matrix is 1-50%.
6. The metal matrix composite material according to claim 1, characterized in that: The thermal conductivity of the nano-diamond particles is 300-3000 W / m·K.
7. The metal matrix composite material according to claim 1, characterized in that: The metal matrix includes at least one metal element selected from the group consisting of tin, antimony, bismuth, aluminum, and zinc; And / or, the grain size of the metal matrix presents a gradient structure that gradually decreases from the inside to the surface.
8. The metal matrix composite material according to claim 1, characterized in that: The metal matrix contains heterogeneous nucleation points; the density of the heterogeneous nucleation points in the metal matrix is 10 8 ~10 12 Pieces / cm 2 .
9. The metal matrix composite material according to claim 1, characterized in that: The substrate material includes a porous material or a non-porous material; the porous material includes at least one of porous aluminum, porous copper, porous nickel or porous stainless steel; the non-porous material includes at least one of aluminum foil, copper foil, titanium foil, stainless steel foil, platinum foil, zinc foil, gold foil, nickel mesh, tungsten mesh, graphene film, carbon cloth or carbon paper.
10. A method for preparing the metal matrix composite material according to any one of claims 1 to 9, characterized in that: The following steps are involved: The solution containing metal salt and nano-diamond particles is used as a plating solution, and the base material is used as an electrode to perform electroplating treatment to obtain the metal-based composite material; the metal elements in the metal salt include the metal elements in the metal matrix.
11. The preparation method according to claim 10, characterized in that: The current density of the electroplating treatment is 1 to 30 mA / cm 2 ; And / or, the deposition time of the electroplating treatment is 5 to 40 minutes.
12. The preparation method according to claim 10, characterized in that: The plating solution also contains gelatin; in the plating solution, the mass content of gelatin is 0.1-5%.
13. A negative electrode material, characterized in that: The invention comprises the metal matrix composite material according to any one of claims 1 to 9, or the metal matrix composite material prepared by the preparation method according to any one of claims 10 to 12.
14. A battery, characterized in that: It comprises a positive electrode material, an electrolyte and the negative electrode material according to claim 13.
15. The battery according to claim 14, characterized in that The positive electrode material includes at least one of graphite, sodium cobalt oxide, sodium nickel manganese oxide, sodium nickel sulfide, sodium manganese oxide, sodium iron phosphate, sodium nickel iron cyanide, vanadium-based oxide or sodium iron fluoride; And / or, the battery includes at least one of a sodium ion battery, a lithium ion battery, a calcium ion battery, a potassium ion battery or a zinc ion battery.
Citation Information
Patent Citations
Diamond heat-conducting composite material and preparation method thereof
CN103966533A
Diamond / metal-matrix composite material as well as preparation method and application thereof
CN113802180A
Metal film layer dispersed with superfine diamond particles, metal material with said film layer and their production method
CN1470678A
Diamond-containing composite metal
JP2012121765A
METHOD AND ELECTROLYTE FOR OBTAINING COMPOSITE METAL-DIAMOND COATINGS, DIAMOND-CONTAINING ADDITIVE AND METHOD OF ITS OBTAINING
RU2007144170A